Stress, sport anxiety, neuroticism, and coping in student-athletes: implications for patient mental health - Contreras, D. W.; Granquist, M. D.; Martin, L. A. (Journal of Athletic Training, 2023)
Key Points - Student-athletes` sport anxiety was positively related to stress and the personality factor of neuroticism. - The personality factor of neuroticism was a negative predictor of emotion-focused coping. - Sport anxiety and stress were predictors of dysfunctional coping.